Total Polyphenol and Flavonoid Content and Antioxidant Capacity of Some Varieties of Persea americana Peels Consumed in Cameroon - Ruth Edwige Kemadjou Dibacto; Boris Ronald Tonou Tchuente; Maxwell Wandji Nguedjo; Yves Martial Tongue Tientcheu; Emilienne Carine Nyobe; Ferdinand Lanvin Ebouel Edoun; Melanie Flore Godam Kamini; Romelle Feumba Dibanda; Gabriel Nama Medoua (The Scientific World Journal)
Fruit peels are increasingly being used as functional foods nowadays. Peelings of twelve varieties of Persea americana fruits consumed in Cameroon were investigated for their phenolic compounds (polyphenols and flavonoids) using three solvents systems, water, ethanol: water (50 : 50 v/v), and ethanol, and antioxidant activity using total antioxidant capacity (TAC), ferric reducing antioxidant power (FRAP), and 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging methods. Total polyphenol, flavonoids, and antioxidant potential of the peels significantly varied with P. americana variety and also with the extraction solvents in the order ethanol > ethanol: water > water. Total phenolic content varied from 2407 (Fuerte florid) to 673 (Semil) mg GAE/g DM, respectively, while flavonoids varied from 986 to 119 mg QE/g DM for Fuerte florid and Hickson varieties, respectively. TAC, respectively, varied between 132.87 and 126.85 mg AAE/g DM with Hass and Semil varieties, respectively. The highest DPPH scavenging capacity was recorded for the ethanolic extract with Lula (86.33%) and the least for the aqueous extract with the Semil (30.11%) variety. With FRAP, the highest capacity was obtained with hydroethanolic extract of Fuerte florid (0.43 mg AAE/g DM) and the least for aqueous extract with the Semil (0.269 mg AAE/g DM) variety. In conclusion, varieties of avocado peels are a good source of antioxidants. Solvent extraction significantly affected the concentration of bioactive compounds but not the potency of the antioxidants. A weakly positive correlation but not significant between the quantity of polyphenol, flavonoid, and antioxidant capacity of avocado peelings was obtained in this study.